2008
DOI: 10.1108/09578230810869275
|View full text |Cite
|
Sign up to set email alerts
|

School context and individual characteristics: what influences principal practice?

Abstract: PurposeAs they operate in complex schools principals must allocate their attention to numerous responsibilities. This paper seeks to ask three questions: how do principals allocate their attention across major realms of responsibility; to what extent do principals in different contexts emphasize different realms of responsibility; and to what extent do individual attributes affect how principals allocate their attention across realms?Design/methodology/approachA cluster analysis is applied to data from a daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(194 citation statements)
references
References 30 publications
9
176
1
8
Order By: Relevance
“…It allows people to follow structured and purposive paths (Bond & Feather, 1988;Sabelis, 2001;Strongman & Burt, 2000;Vodanovich & Seib, 1997) to gain sufficient insight to distribute time efficiently across multiple activities (King et al, 1986), which helps individuals to maximise and enhance their intellectual productivity (Britton & Tesser, 1991). One study of principals and their time allocation practices found that principals allocate their time across a variety of responsibilities, including matters related to employees, budgeting, student services, external relations and a host of other areas (Goldring et al, 2008;Grissom, Loeb & Master 2013;Horng, Klasik & Loeb, 2010;Spillane, Camburn & Pareja, 2007;Spillane & Hunt, 2010). Principals also spend time on organisational management, including, specifically, personnel management, budgeting and other school outcomes (Horng, Klasik, & Loeb, 2010;May, Huff, & Goldring, 2012).…”
Section: Time Management and Its Scopementioning
confidence: 99%
“…It allows people to follow structured and purposive paths (Bond & Feather, 1988;Sabelis, 2001;Strongman & Burt, 2000;Vodanovich & Seib, 1997) to gain sufficient insight to distribute time efficiently across multiple activities (King et al, 1986), which helps individuals to maximise and enhance their intellectual productivity (Britton & Tesser, 1991). One study of principals and their time allocation practices found that principals allocate their time across a variety of responsibilities, including matters related to employees, budgeting, student services, external relations and a host of other areas (Goldring et al, 2008;Grissom, Loeb & Master 2013;Horng, Klasik & Loeb, 2010;Spillane, Camburn & Pareja, 2007;Spillane & Hunt, 2010). Principals also spend time on organisational management, including, specifically, personnel management, budgeting and other school outcomes (Horng, Klasik, & Loeb, 2010;May, Huff, & Goldring, 2012).…”
Section: Time Management and Its Scopementioning
confidence: 99%
“…There is more recent attention on the effects of contexts on instructional leadership with increasing evidence that contexts can influence principals' practices (Goldring, Huff, May, & Camburn, 2008;Hallinger, 2011a;Louis, Leithwood, et al, 2010;Louis & Robinson, 2012). The school community is a complex environment, and many contextual factors at the state and local levels shape principals' perceptions and actions as leaders.…”
Section: Contextual Influences On Principals' Instructional Leadershipmentioning
confidence: 99%
“…They found that the principal had to confront not only fiscal and organizational challenges, but community poverty, violence, and professional apathy. Principals' attention on different school and community factors can affect the amount of time they actually focus on instructional leadership (Goldring et al, 2008).…”
Section: School-levelmentioning
confidence: 99%
See 2 more Smart Citations